Influence of hormonal contraceptives and the occurrence of stroke: integrative review - Adman Câmara Soares Lima; Larissa Castelo Guedes Martins; Marcos Venícios de Oliveira Lopes; Thelma Leite de Araújo; Francisca Elisângela Teixeira Lima; Priscila de Souza Aquino; Escolástica Rejane Ferreira Moura
ABSTRACT Objective: To identify scientific evidence regarding the influence of hormonal contraceptive use and the occurrence of stroke. Method: Integrative review of the literature, through database search using the descriptors "contraceptive agents", "contraceptive devices", "contraceptives, Oral" and "Stroke". Original studies in Portuguese, Spanish and English, published in full and available online were included. Studies that did not answer our guiding questions and duplicated studies were excluded. Results: Women using combined oral contraceptives have higher risk of stroke, even with a lower hormonal dosage and different types of progestogen, regardless of the duration of use. The use of contraceptives associated with smoking, hypertension, migraine, hypercholesterolemia, obesity and sedentary lifestyle increases the chance of stroke. Contraceptive patch and vaginal ring are associated to increased risk. Conclusion: Use of combined hormonal contraceptives, except for the injectable and the transdermal ones, increases the chance of occurrence of the event. Progestogen-only contraceptives were considered safe.